Cleistopholine Isolated From Enicosanthellum Pulchrum Exhibits Apoptogenic Properties In Human Ovarian Cancer Cells - Noraziah Nordin; Nazia Abdul Majid; Syam Mohan; Firouzeh Dehghan; Hamed Karimian; Mashitoh Abdul Rahman; Hapipah Mohd Ali; Najihah Mohd Hashim (Elsevier, 2024)
Background: Cleistopholine is a natural alkaloid present in plants with numerous biological activities. However, cleistopholine has yet to be isolated using modern techniques and the mechanism by which this alkaloid induces apoptosis in cancer cells remains to be elucidated.